Demagnetizer Frequency Converter - G. I. Goulkov; A. A. Migdalionok; Rashid Shaibi (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers a power scheme and a control system of  two-member frequency converter with voltage inverter which is designed for power supply of a bearing ring demagnetizer inductor. An algorithm for commutation of power keys is proposed in the paper. The algorithm makes it possible to obtain an inductor current which is close to the given current at low commutation frequency of power equipment.  Simulation modeling within the system of computer «Mathlab Simulink» modeling has been applied with the purpose to evaluate the algorithm quality. The obtained charts of frequency converter electrical variables have shown practical coincidence of the given and actual currents that testifies about high efficiency of the proposed commutation algorithm. In addition to this an analytical expression for calculating filter capacity of  demagnetizer inductor  voltage inverter has been developed in the paper.